Pāreṅgā : byākaraṇa, racanābaḷī, o śabdakosha - Mahāpātra, Sasmitā (Ādibāsī bhāshā adhyayanamāḷā, 1994)
Grammar, composition, and dictionary of the Parengi language belonging to the Munda languages and spoken by Parenga people of Koraput District, Orissa.